DIGITALISATION OF THE INSURANCE SECTOR: TRENDS AND TECHNOLOGIES - Tangirberdiyeva Gulchekhra Rakhimzhanovna (European Science Publishing, 2025)
This paper aims to analyse the digitalisation processes in the insurance industry, which is undergoing transformation under the influence of modern technologies and changing consumer expectations. InsurTech is attracting more and more attention as an important factor in the transformation of the insurance industry. Key trends are discussed, including the introduction of artificial intelligence (AI), Big Data, blockchain, the Internet of Things (IoT) and telematics, as well as their impact on optimising business processes, increasing customer focus and reducing operational risks. Particular attention is paid to the application of AI to automate underwriting, risk assessment and claims processing, as well as the use of blockchain to ensure transparency and security of transactions. The article analyses the benefits and challenges of digitalisation, including cybersecurity, regulatory issues and the need to adapt traditional business models.
Keywords: Digitalisation, insurance sector, insurtech, artificial intelligence, machine learning, big data, blockchain, Internet of Things (IoT), telematics, cybersecurity, digital transformation.